LIST OF THE CULICOIDES OF THE WORLD - VARGAS, LUIS (Hospital Spanish, CD MEXICO, DF, MEX, 1950)
Injn of ocular liquids and of hyaluronic acid into axolotls notably accelerated speed of metamorphosis as compared with that produced by injn of thyroxin Huxley's theory that the specific reactivity of tissues to thyroxin is involved in metamorphosis i
REV SOC MEX HIST NAT
Keywords: LIST, CULICOIDES, WORLD; CIENCIAS DE LA VIDA; BIOLOGIA DE LOS INSECTOS (ENTOMOLOGIA); MORFOLOGIA DE LOS INSECTOS